How is philosophy in science possible? - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
The Michael Heller’s article entitled “How is philosophy in science possible?” was originally published in Polish in 1986 (see Heller, 1986) and then translated into English by Bartosz Brożek and Aeddan Shaw and published in 2011 in the collection of essays entitled Philosophy in Science. Methods and Applications (Heller, 2011). This seminal paper has founded further growth of the ‘philosophy in science’ and become the reference point in the methodological discussions, especially in Poland. On the 40th anniversary of Philosophical Problems in Science we wanted to make this paper freely available to the international public by reprinting its English version. In this issue it is followed by two additional articles-commentaries (by Paweł Polak and Kamil Trombik).